Співвідношення редокс-форм убіхінону в мітохондріях нирок щурів за умов різної забезпеченості раціону нутрієнтами. - Ursatyi, Mariya; Voloshchuk, Oksana; Kopylchuk, Galina (My University, 2021)
The aim of work was to study the content of total ubiquinone and the ratio of its redox forms in the mitochondria of the kidneys of rats under conditions of different supply of protein and sucrose in the diet. It was found that the most pronounced decrease in the content of total ubiquinone and the redistribution of its redox forms (a decrease in the content of reduced ubiquinone by half against the background of an increase in the content of oxidized ubiquinone by 1.5 times) in kidney mitochondria is observed in animals fed a diet with a high content of sucrose against the background of alimentary deprivation protein. The established changes can be considered as prerequisites for the development of renal mitochondrial dysfunction under the studied conditions
THE RATIO OF UBIQUINON REDOX FORMS IN THE RAT KIDNEY MITOCHONDRIA UNDER CONDITIONS OF DIFFERENT NUTRIENT SUPPLY
Keywords: нутрієнти; мітохондрії